Penyuluhan Pembelajaran Mendalam Berbasis Nilai Budaya di TK Kemala Bhayangkari Kabupaten Gowa - Musi, Muhammad Akil; Hajerah, Hajerah; Kurnia R., Rika; Asti, A. Sri Wahyuni; Lismayani, Angri (Program Studi Manajemen FEB UNM, 2026)
This community service activity aims to enhance the understanding of kindergarten teachers at TK Kemala Bhayangkari, Gowa Regency, regarding deep learning approaches based on cultural values. The method used was a counseling and training approach through participatory action research (PAR) involving 10 kindergarten teachers as participants. Data were collected through observation, interview, and questionnaire instruments. The activity was carried out on January 26, 2026, with a focus on integrating local cultural values into learning activities for early childhood. The results showed a significant increase in teachers’ understanding and ability to design culturally relevant deep learning activities. It is concluded that the counseling program effectively improved teachers’ competence in implementing culturally grounded deep learning in the early childhood context.